2021
DOI: 10.1002/vzj2.20087
|View full text |Cite
|
Sign up to set email alerts
|

Pore‐scale modeling of microbial activity: What we have and what we need

Abstract: Under water-unsaturated conditions, environmental factors (e.g., substrate, nutrients, O 2 , water activity, and porous structure) controlling microbial activity are highly variable in space and time. The physical structure of porous media (pore size distribution and pore arrangements) has been considered to have a significant role in nutrient (either substrate and/or its reaction partners like O 2) fluxes. Understanding what eventually controls microbial activity thus requires a sound description of the physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 156 publications
(200 reference statements)
0
7
0
Order By: Relevance
“…The geometry of the pore space in many soils may be so convoluted as to preclude microorganisms, and even their exoenzymes, access to potential substrates. These insights are increasingly reflected by a new generation of mathematical models that take the microscale heterogeneity of soils explicitly into account when describing the fate of organic matter (e.g., Falconer et al, 2015;Golparvar et al, 2021;König et al, 2020;Pot et al, 2022;Vogel et al, 2015).…”
Section: Mineralization Kinetics: Patterns and Inherent Complexitymentioning
confidence: 99%
“…The geometry of the pore space in many soils may be so convoluted as to preclude microorganisms, and even their exoenzymes, access to potential substrates. These insights are increasingly reflected by a new generation of mathematical models that take the microscale heterogeneity of soils explicitly into account when describing the fate of organic matter (e.g., Falconer et al, 2015;Golparvar et al, 2021;König et al, 2020;Pot et al, 2022;Vogel et al, 2015).…”
Section: Mineralization Kinetics: Patterns and Inherent Complexitymentioning
confidence: 99%
“…Unsaturated reactive transport in porous media has been the holy grail of groundwater studies where the redox processes play a deterministic role in the fate of nutrients (Golparvar, Kästner, and Thullner 2021;Pot et al 2022). Oxygen as the main oxidant for the aerobic organisms diffuses from the gaseous phase into the aqueous phase.…”
Section: Biogeochemical Reactionsmentioning
confidence: 99%
“…Most of the studies in this field use macroscopic unsaturated solute transport models that solve Richard's equation (Richards 1931;van Genuchten 1980) at continuum scale, such as HYDRUS-PHREEQC (Jacques et al 2018) and MIN3P (Mayer, Frind, and Blowes 2002;Sihota and Ulrich Mayer 2012). Therefore, lack of a sophisticated unsaturated reactive pore-network model has been noted in which the redox processes are linked to the variability of water saturation in pores, and the reduction-oxidation reactions are mainly regulated by soil water content, next to other soil properties (Golparvar, Kästner, and Thullner 2021).…”
Section: Biogeochemical Reactionsmentioning
confidence: 99%
“…To avoid this lumping together a new generation of SOM decomposition models has been developed, accounting for the three-dimensional architecture of soil and the heterogeneity of the distributions of microorganisms, water, air, SOM and reactive surfaces at the level of microbial habitats (Baveye et al, 2018). In two recent mini-reviews, König, Vogel, Harms, and Worrich (2020) reported on microscale models with a special focus on spatiotemporal dynamics of bacteria and bacterial functions in soil microhabitats, and Golparvar, Kästner, and Thullner (2021) reported on microscale models of reactive transport modelling in porous media.…”
Section: Introductionmentioning
confidence: 99%